2018
DOI: 10.1021/acs.joc.8b00046
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Asymmetric Dearomative Cycloaddition for Construction of Optically Active Pyrroloindoline and Cyclopentaindoline Derivatives: Access to 3a-Aminopyrroloindolines

Abstract: Asymmetric dearomative [3 + 2] cycloaddition reactions of 3-nitroindoles with vinyl aziridine and vinyl cyclopropanes have been respectively successfully developed in the presence of a chiral box/Pd(0) complex. A series of enantiomerically enriched 3a-nitro-hexahydropyrrolo[2,3-b]indole and 8b-nitrohexahydrocyclopenta[b]indole derivatives containing three contiguous chiral centers are smoothly obtained in high yields with satisfactory regio-, chemo-, and enantioselectivity. Remarkably, the synthetic utility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…That same year, Wang group independently reported Pd‐catalyzed asymmetric dearomative [3+2] cycloaddition reactions of 3‐nitroindoles with vinyl aziridine and vinyl cyclopropanes in the presence of a chiral indane‐box ligand. A diverse of optically active 3a‐nitro‐hexahydropyrrolo[2,3‐ b ]indole and 8b‐nitrohexahydrocyclopenta[ b ]indole derivatives with three contiguous chiral centers were synthesized in high yields with moderate to excellent diastereo‐ and enantioselectivities [34] . Simultaneously, Shi and co‐workers developed Pd‐catalyzed asymmetric dearomative [3+2] cycloaddition of 3‐nitroindoles with vinyl cyclopropanes by using a chiral phosphoramidite ligand, affording chiral cyclopenta[ b ]indoline scaffolds with high enantioselectivities [35] .…”
Section: Palladium‐catalyzed Asymmetric Cycloadditions Of Activated Alkenesmentioning
confidence: 99%
“…That same year, Wang group independently reported Pd‐catalyzed asymmetric dearomative [3+2] cycloaddition reactions of 3‐nitroindoles with vinyl aziridine and vinyl cyclopropanes in the presence of a chiral indane‐box ligand. A diverse of optically active 3a‐nitro‐hexahydropyrrolo[2,3‐ b ]indole and 8b‐nitrohexahydrocyclopenta[ b ]indole derivatives with three contiguous chiral centers were synthesized in high yields with moderate to excellent diastereo‐ and enantioselectivities [34] . Simultaneously, Shi and co‐workers developed Pd‐catalyzed asymmetric dearomative [3+2] cycloaddition of 3‐nitroindoles with vinyl cyclopropanes by using a chiral phosphoramidite ligand, affording chiral cyclopenta[ b ]indoline scaffolds with high enantioselectivities [35] .…”
Section: Palladium‐catalyzed Asymmetric Cycloadditions Of Activated Alkenesmentioning
confidence: 99%
“…Shi and colleagues carried out dearomative [3+2] cyclization reactions of 3‐nitroindoles 71 with 2‐vinylcyclopropane‐1,1‐dicarbonitrile 102 using a chiral catalysis system consisting of Pd(dba) 2 and the chiral P,N‐ligand 104 ; these reactions afforded cis ‐cyclopentane‐fused indolines 103 with variable diastereoselectivities and good enantioselectivities (Scheme a) . In contrast, Wang and co‐workers used the chiral indane‐BOX ligand 107 to induce asymmetric dearomative cyclization reactions of 3‐nitroindoles 71 with 2‐vinylcyclopropane‐1,1‐dicarboxylates 105 , which gave high yields of trans ‐cyclopentane‐fused indolines 106 (Scheme b) …”
Section: [3+2] Cyclizationsmentioning
confidence: 99%
“…These reactions gave trans ‐pyrroloindolines 109 in high yields with high diastereoselectivities in most cases, and cis products could be obtained from C‐4 substituted indoles. Very recently, Wang and co‐workers achieved an enantioselective version of this reaction with asymmetric catalysis by Pd 2 (dba) 3 /chiral BOX 111 , which afforded an access to the trans adducts 110 with satisfactory yields and stereoselectivities (Scheme a); and Hou and co‐workers described another enantioselective version that used Pd 2 (dba) 3 and chiral diphosphine 113 as dual catalysts and allowed for stereocontrolled synthesis of cis ‐ 112 (b, Scheme ) …”
Section: [3+2] Cyclizationsmentioning
confidence: 99%
“…Recent studies have shown that the substitution at the C-3 position with electron-withdrawing groups (3-EWG-indoles) not only endows these structures with important pharmaceutical/therapeutic activities [13][14][15][16][17][18][19][20][21], but also it converts them into versatile synthetic molecular platforms in heterocyclic chemistry, such as, in dearomatization-based synthetic disconnections [22]. The catalytic asymmetric dearomatization of 3-nitroindoles constitutes an iconic example of this synthetic potential [23][24][25][26][27][28][29][30][31][32][33][34]. The most traditional synthetic approach to these functionalized indoles relies on the Friedel-Crafts acylation of preformed indoles [35][36][37].…”
Section: Introductionmentioning
confidence: 99%